Bone Regeneration: Mini-Review and Appealing Perspectives - Sylvain Le Grill; Fabien Brouillet; Christophe Drouet (Bioengineering)
Bone is a natural mineral-organic nanocomposite protecting internal organs and allowing mobility. Through the ages, numerous strategies have been developed for repairing bone defects and fixing fractures. Several generations of bone repair biomaterials have been proposed, either based on metals, ceramics, glasses, or polymers, depending on the clinical need, the maturity of technologies, and knowledge of the natural constitution of the bone tissue to be repaired. The global trend in bone implant research is shifting toward osteointegrative, bioactive and possibly stimuli-responsive biomaterials and, where possible, resorbable implants that actively promote the regeneration of natural bone tissue. In this mini-review, the fundamentals of bone healing materials and clinical challenges are summarized and commented on with regard to progressing scientific discoveries. The main types of bone-healing materials are then reviewed, and their specific relevance to the field is reminded, with the citation of reference works. In the final part, we highlight the promise of hybrid organic-inorganic bioactive materials and the ongoing research activities toward the development of multifunctional or stimuli-responsive implants. This contribution is expected to serve as a commented introduction to the ever-progressing field of bone regeneration and highlight trends of future-oriented research.